Electrochemical synthesis of TiO2/Graphene oxide composite films for photocatalytic applications - Anderson Guimarães de Oliveira (2016)
This paper presents a novel TiO2-Graphene composite film one-step preparation method by electrochemical synthesis. The films were prepared on a Ti substrate by electrochemical deposition from a GO and Ti (IV) aqueous solution. For comparison, pure TiO2 on a Ti substrate was obtained by the same electrochemical method. The as-prepared samples were characterized by X-ray diffraction, scanning electron microscopy, Raman spectroscopy, photoluminescence and ultravioletevisible spectrophotometry. The photocatalytic properties of the films were investigated for the discoloration of Reactive Yellow 145 dye. The results showed that the TiO2-Graphene oxide composite film presented photocatalytic activity almost twice as high as that observed for the TiO2 film. In addition, the TiO2-Graphene oxide composite film presented better stability and recyclability, retaining its catalytic efficiency (z70%) even after 15 cycles. Published by Elsevier B.V.